ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK SARANG BURUNG WALET TERHADAP PENERIMAAN PAJAK DAERAH DI KABUPATEN MINAHASA TENGGARA - Rotulung, Frandy Demsy Abed; Lambey, Linda; Pinatik, Sherly (Universitas Sam Ratulangi, 2018)
Swallow's Nest Tax is a tax on the activities of taking Swallow's Nest Business. Regional Government of Southeast Minahasa District collects the local taxes. The purpose of this study is to measure the effectiveness and contribution of tax revenue swallow's nest against local tax revenue of Southeast Minahasa District. Data analysis method in this research is using quantitative descriptive analysis method, based on effectiveness ratio analysis and contribution. The effectiveness level of Swallow’s Nest tax in 2015 only amounted to 68.75% still classified as less effective, in 2016 is still classified as less effective with a percentage of 80.00%, in 2017 increased to 196.40% effectively. Contributions tax of Swallow’s Nest against local tax revenue of South Minahasa District still on the very less ratio. Fluctuation of effectiveness and contribution of Swallow’s Nest tax against local tax revenue of Southeast Minahasa District can be surmountable or can be improved.Keywords: Swallow's Nest Tax, Local Tax, Effectiveness, Contribution